Thermally stable and highly conductive SAMs on Ag substrate: the impact of the anchoring group - Wróbel, Mateusz; Żaba, Tomasz; Sauter, Eric; Krawiec, Mariusz; Sobczuk, Joanna; Terfort, Andreas; Zharnikov, Michael; Cyganik, Piotr (Advanced electronic materials, 2021)
Self-assembled monolayers (SAMs) on metal substrates are an important part of modern interfacial chemistry and nanotechnology. The robustness of SAMs strongly depends on their thermal stability, which, together with electric conductivity, crucial for their applications in molecular/organic electronics. In this context, using a multidisciplinary approach, the structure, stability, and conductivity properties of conjugated aromatic SAMs featuring the naphthalene backbone and S, Se, or COO group, mediating bonding to the Ag substrate are addressed. Whereas thermal stability of these SAMs exhibits a strong dependence on anchoring group, their conductivity is similar, which is rationalized by tentative model considering redistribution of charge density along the molecular framework. The thermal stability of model naphthalenethiol SAM, emphasized by desorption energy of ≈1.69 eV, is better than that of typical N-heterocyclic carbene (NHC) monolayers considered currently as the most stable SAMs on metal substrates. However, in contrast to NHC SAMs, which are highly insulating, the naphtalene-based SAM, with S, Se or COO anchoring groups, are highly conductive, even in comparison with analogous oligophenyl SAMs (by a factor of 10). A unique combination of the ultimate thermal stability and superior conductivity for the naphthalenethiol SAM on Ag makes it highly attractive for applications.